The Regional Comprehensive Economic Partnership (RCEP) agreement: Economic implications for the EU27 and Austria - Robert Stehrer; Nina Vujanovic (FIW - Research Centre International Economics, 2022)
The RCEP agreement, signed between ASEAN+3, New Zealand and Australia, forms the largest trade bloc in history, and will likely change the gravity of trade more towards Asia. This will pose large implications for its members that, due to economic and trade diversities, may not incur all economic benefits equally. This policy brief demonstrates that the countries encompassing the current trade bloc are large trade partners of the EU and Austria, and this trade embeddedness has been on the rise. High tech industries are particularly trade dependent on imports from this trade bloc, while significant value added from China is embodied in EU and Austrian service and goods exports. The assessment based on Caliendo-Parro is that due to formation of the bloc, trade with the EU may decline by -1%. Austrian export will suffer slightly more (-1.2%). However, more positive welfare effects might be generated from successful EU FDI inflows to the newly formed trade bloc, when possible.
Keywords: 330